The predicted risk of head injury from fall-related impacts on to third-generation artificial turf and grass soccer surfaces: A comparative biomechanical analysis - Theobald, P.; Whitelegg, L.; Nokes, L. M. D.; Jones, M. D. (Sports Biomechanics, 2010)
The risk of soccer players sustaining mild traumatic brain injury (MTBI) following head impact with a playing surface is unclear. This study investigates MTBI by performing headform impact tests from varying heights onto a range of third-generation artificial turf surfaces. Each turf was prepared as per manufacturers specifications within a laboratory, before being tested immediately following installation and then again after a bedding-in period. Each turf was tested dry and when wetted to saturation. Data from the laboratory tests were compared to an in situ third-generation surface and a professional grass surface. The surface performance threshold was set at a head impact criterion (HIC) = 400, which equates to a 10% risk of the head impact causing MTBI. All six third-generation surfaces had a >10% risk of MTBI from a fall >0.77 m; the inferior surfaces required a fall from just 0.46 m to have a 10% MTBI risk. Wetting the artificial turf did not produce a statistically significant improvement (P > 0.01). The in situ third-generation playing surface produced HIC values within the range of bedded-in experimental values. However, the natural turf pitch was the superior performer - necessitating fall heights exceeding those achievable during games to achieve HIC = 400.